Pengaruh Kecepatan Pengelasan terhadap Sifat Mekanik Sambungan Alumunium Paduan 5052 pada Proses Friction Stir Welding [Effect of Welding Speed to Mechanical Properties on Friction Stir Welding of Aluminum 5052-H32] - Tarmizi; Wahid, Robi Farid Abdurachman; Irfan (Jurnal Metalurgi, 2019)
One of the causes of FSW (friction stir welding) defects is improper welding speed, which will cause void defects in metal joints. FSW research with welding speed variations is done to overcome these problems. This study was conducted using aluminum plate 5052-H32 with a thickness of 10 mm and a constant tool rotation of 1500 rpm. In the current research show that the use of welding speed 38, 64, and 83 (mm / min) with clockwise threaded cylinder tool produce a large tunnel defect along the joint line. In the use of the counterclockwise threaded cylinder tool with welding speed 22 mm/min resulted in connection with smaller voids along the joint line. All experimental results produce flash defects, which are still in AWS D17.3 standards. Increasing welding speed qualitatively provide more significant defect.